(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Depression and anxiety are prevalent in BC patients and may affect surgical factors. It is for this reason that it is important for health-care providers to understand the above correlation in view of enhancing quality patient care as well as the success of surgeries. Aim: The purpose of this work is to identify the correlation between the severity of persistent psychological distress and surgery outcomes in women with breast cancer, who have undergone mastectomy. Methods: An exploratory cross sectional descriptive study was undertaken with 300 women from a tertiary hospital who were to undergo mastectomy. The sample size was determined using the WHO sample sized estimate for prevalence studies. Self-reported psychological distress was measured by the Hospital Anxiety and Depression Scale (HADS) and surgical efficacy was judged by post operative complication, length of convalescence and patient satisfaction. Information obtained was analyzed using statistical software and results highlighted in colored tables, graphs and pie charts. Results: Persistent psychological distress had higher outcomes of being severely affected and these was strongly associated with adverse surgical outcomes. Postoperative distress was associated with higher complication rates (p<0.05), longer length of stay and lower satisfaction scores. Psychological distress was experienced by 35% of the participants, with anxiety being more cloudsome than depression. Conclusion: Poor health-related quality of life due to severe persistent psychological distress reduces surgical success in women undergoing mastectomy for breast cancer. Adding psychological testing and treatment into the context of preparation for surgery could improve the chances of a successful operation and a patient’s quality of life.